PENGARUH MACAM PUPUK CAIR DAN PENGGUNAAN SURFAKTAN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max(L)Merril) DENGAN TEKNOLOGI SONIC BLOOM - maesaroh maesaroh; Istirochah Pujiwati; Anis Sholihah (AGRONISMA, 2022)
The aim of this study was to determine the grouth and yield of soybean (Glycine max (L.) Merril) through compost tea fertilization at various concentrations compared to inorganic growmore fertilizer with sonic bloom technology. The research was carried out in a greenhouse (green house) Campus II of Malang Agricultural Development Polytechnic, Tanjungrejo Village, Sukun District, Malang City with an altitude of Â± 445 meters above sea level. The analysis was carried out at the Plant Improvement Laboratory, Muhammadiyah University, Malang. The study was conducted from January to April 2021. This study used a Factorial Randomized Block Design (RBD) experiment consisting of 2 factors. Factor 1 kinds of liquid fertilizer (P) consists of 5 levels: P0 (Without fertilizer), P1 (Inorganic fertilizer Growmore). P2 (organic compost tea fertilizer 5%), P3 (10% organic compost tea fertilizer), P4 (15% organic compost tea fertilizer). Factor 2 using surfactant, consisting of 2 levels of S0 (without surfactant) S1 (with surfactant) obtained 10 combinations of 2 factors, each treatment was repeated 3 times with 4 samples. The results showed that there was an interaction between types of liquid fertilizer treatment and the use of surfactants on soybean plant growth parameters of plant length, productive branches, leaf area and number of leaves, while the yield component significantly affected the weight of 100 seeds. The use of compost tea liquid fertilizer with a concentration of 5% gave a significant effect on the growth of soybean plants, the parameters of leaf area, number of leaves, while the yield had a significant effect on the parameters of the weight of 100 seeds. The administration of the recommended dose of surfactant on the growth of soybean plants had a significant effect on the number of leaves parameters. However, on soybean yields, using surfactant did not have a significant effect.Key words : Soybean, compost tea, surfactant, growmore, sonic bloom.